Sulfaphenazole reduces thermal and pressure injury severity through rapid restoration of tissue perfusion - Christopher T. Turner; Megan Pawluk; Juliana Bolsoni; Matthew R. Zeglinski; Yue Shen; Hongyan Zhao; Tatjana Ponomarev; Katlyn C. Richardson; Christopher R. West; Anthony Papp; David J. Granville (Scientific Reports, 2022)
Abstract Pressure injuries, also known as pressure ulcers, are regions of localized damage to the skin and/or underlying tissue. Repeated rounds of ischemia–reperfusion (I/R) have a major causative role for tissue damage in pressure injury. Ischemia prevents oxygen/nutrient supply, and restoration of blood flow induces a burst of reactive oxygen species that damages blood vessels, surrounding tissues and can halt blood flow return. Minimizing the consequences of repeated I/R is expected to provide a protective effect against pressure injury. Sulfaphenazole (SP), an off patent sulfonamide antibiotic, is a potent CYP 2C6 and CYP 2C9 inhibitor, functioning to decrease post-ischemic vascular dysfunction and increase blood flow. The therapeutic effect of SP on pressure injury was therefore investigated in apolipoprotein E knockout mice, a model of aging susceptible to ischemic injury, which were subjected to repeated rounds of I/R-induced skin injury. SP reduced overall severity, improved wound closure and increased wound tensile strength compared to vehicle-treated controls. Saliently, SP restored tissue perfusion in and around the wound rapidly to pre-injury levels, decreased tissue hypoxia, and reduced both inflammation and fibrosis. SP also demonstrated bactericidal activity through enhanced M1 macrophage activity. The efficacy of SP in reducing thermal injury severity was also demonstrated. SP is therefore a potential therapeutic option for pressure injury and other ischemic skin injuries.